Mulheres indígenas apinajés: trajetórias socioespacias em Tocantinópolis (TO) - TORRES, Carina Alves (2024)
The present dissertation has as general objective to analyze how the socio-spatial trajectories of Apinajé indigenous women as the city of Tocantinópolis are constructed. The observed fact is that women of this ethnicity build spatialities with the urban context, in this sense I start from the perspective of oral history of life and participant observation to understand how the women of the Itelvina matriarch and leadership family establish socio-spatial trajectories from the village of São José to the city . The women surveyed are recurrently in the city for various purposes, such as shopping, studying, playing football, doctor's appointments, parties and other purposes. Through field experience and bibliographic research I noticed that the gender issue in the Apinajé ethnic group has undergone several social changes over the years, one of which is in the political sphere, women are actively participating in the political structure and socio-cultural demands. The socio-spatial trajectories of the Apinajé women with the city of Tocantinópolis, are marked by shopping in shops, leisure, meetings, studies and medical consultations, with decades prior to women not building spatialities with the urban territory, as in the present day, demonstrating interethnic contacts and social changes in the gender issue in this ethnic group.